2006
DOI: 10.1016/s0022-5347(05)00039-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prevalence of Urinary Incontinence by Race/Ethnicity

Abstract: Significant differences in the adjusted risk of stress incontinence among Hispanic, white, black and Asian-American women suggest the presence of additional, as yet unrecognized, risk or protective factors for stress incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
151
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 213 publications
(162 citation statements)
references
References 20 publications
9
151
1
1
Order By: Relevance
“…Interestingly, in the RRISK cohort, Latina females had the highest prevalence of weekly or greater urinary incontinence, followed by white, African-American, and Asian-American females (36, 30, 25, and 19 percent, respectively, P < 0.001). 16 The decreased prevalence of FI and increased prevalence of urinary incontinence in Latinas could be a result of reporting bias or other unmeasured factors not included in our analysis. Future studies of prevalence using larger sized Latina populations and anorectal physiology studies pertaining to FI in Latinas may further clarify this new finding.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, in the RRISK cohort, Latina females had the highest prevalence of weekly or greater urinary incontinence, followed by white, African-American, and Asian-American females (36, 30, 25, and 19 percent, respectively, P < 0.001). 16 The decreased prevalence of FI and increased prevalence of urinary incontinence in Latinas could be a result of reporting bias or other unmeasured factors not included in our analysis. Future studies of prevalence using larger sized Latina populations and anorectal physiology studies pertaining to FI in Latinas may further clarify this new finding.…”
Section: Discussionmentioning
confidence: 94%
“…Details of the recruitment have been separately reported. 16 Data on fecal incontinence were collected by self-report questionnaires. Fecal incontinence was assessed by the question "During the last 12 months, how often have you experienced leakage of stool (bowel movements), accidents, or soiling because of inability to control passage of stool (bowel movements) until you reach the toilet?"…”
Section: Methodsmentioning
confidence: 99%
“…These risk factors are consistent with other population-based studies that evaluated racial differences. 6,20 Despite adequate representation of both racial groups, there was little evidence to support the idea that risk factors for UI differed between black and white women. This is in contrast to earlier work by Bump et al showing different risk factors for black versus white women; however, his study acknowledged that its small sample size limited its ability to make conclusions about racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior reports, we found different types of UI reported by each racial group. 6,14,20,21 White women reported stress incontinence symptoms more commonly than black women, whereas twice as many black women reported symptoms of urge incontinence as compared to white women. In a large cohort study from a health maintenance organization, Thom found similar results for stress urinary incontinence symptoms, but in their population, the difference in urge UI by race was relatively small and not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation